2009
DOI: 10.1194/jlr.m800300-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Selective decrease of bis(monoacylglycero)phosphate content in macrophages by high supplementation with docosahexaenoic acid

Abstract: Bis(monoacylglycero)phosphate (BMP) is a unique phospholipid (PL) preferentially found in late endosomal membranes, where it forms specialized lipid domains. Recently, using cultured macrophages treated with anti-BMP antibody, we showed that BMP-rich domains are involved in cholesterol homeostasis. We had previously stressed the high propensity of BMP to accumulate docosahexaenoic acid (DHA), compared with other PUFAs. Because phosphatidylglycerol (PG) was reported as a precursor for BMP synthesis in RAW macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 52%
“…C18:1 is a major BMP fatty acid in many cell types (69)(70)(71)(72)(73)(74). In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ).…”
Section: Discussionmentioning
confidence: 99%
“…___________________________________________________________________________ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 The lysophospholipid named LBPA (lysobis-phosphatidic acid), also called BMP (bis-(monoacylglycero)-phosphate) starts to appear at the stage of MVB along the endocytic track, whereas its precursor, phosphatidylglycerol (PG) is biosynthesized in the mitochondria. Exogenous PG can be converted into LBPA in the MVB [28]. LBPA regulates the ILV turn-over within the MVB [27].…”
Section: Resultsmentioning
confidence: 99%
“…LBPA is biosynthesized from phosphatidylglycerol (PG) whose biosynthesis occurs in the mitochondria. PG would then be transported to the MVB (Fig 2) which appears to contain the conversion machinery of PG into LBPA since adding PG-containing liposomes in the endocytic track enhances the amount of LBPA recovered in MVB [28].…”
Section: Sorting Lipids In Exosomes (Figure 2)mentioning
confidence: 99%
“…Bouvier et al (38) found that the C 22:6 /C 22:6 species of BMP was highly sensitive to oxidative stress, showing a significant decrease in macrophages after exposure to oxidative stresses, although many studies demonstrated the dramatic increase of BMP levels in the tissue of animals and humans with the lysosomal disorder, such as Niemann-Pick C disease, certain druginduced lipidosis, and anti-phospholipid syndrome (39,40). We carried out LC/MS analysis to measure the BMP levels, as compared with our current quantitative BMP measurement.…”
Section: Journal Of Biological Chemistry 27439mentioning
confidence: 99%